2019
DOI: 10.2174/1567205016666190228121157
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of the PERK-Dependent Unfolded Protein Response Signaling Pathway Involved in the Pathogenesis of Alzheimer’s Disease

Abstract: <P>Objectives: There is a body of evidence that neurodegenerative disease entities are directly correlated with the perturbations on the molecular level. Hence, the ER stress-mediated Unfolded Protein Response (UPR) is activated resulting in PERK-dependent phosphorylation of the Eukaryotic initiation factor 2 (eIF2α). Thus, the levels of ATF4 and CHOP proteins are significantly increased, which subsequently switches the pro-adaptive branch of the UPR into the pro-apoptotic directly leading to neuronal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…These genes are involved in resistance to cancer therapy (Tirado-Hurtado, Fajardo, & Pinto, 2018), or in the initiation of apoptotic cell death after long-term activation of the ER stress responses (Rozpędek et al, 2016). Furthermore, TRIB3 has been suggested as a novel marker for prognosis in colorectal cancer (Ohoka, Yoshii, Hattori, Onozaki, & Hayashi, 2005), and its down-regulation may explain the anti-proliferative activity of the extract.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…These genes are involved in resistance to cancer therapy (Tirado-Hurtado, Fajardo, & Pinto, 2018), or in the initiation of apoptotic cell death after long-term activation of the ER stress responses (Rozpędek et al, 2016). Furthermore, TRIB3 has been suggested as a novel marker for prognosis in colorectal cancer (Ohoka, Yoshii, Hattori, Onozaki, & Hayashi, 2005), and its down-regulation may explain the anti-proliferative activity of the extract.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…However, the actual mechanism of action of the inhibitor is yet to be identified. It would also be intriguing to investigate whether this mentioned compound in fact exerts neuroprotective effects in animal models of not only AD but also other neurodegenerative diseases, including PD, ALS, and prion disease [289].…”
Section: Ldn-0060609mentioning
confidence: 99%
“…The newest data have reported that aggregation of misfolded and unfolded proteins within the lumen of the ER is strictly associated with the pathogenesis of multiple neurodegenerative disorders, as it may affect numerous cell signaling pathways and neuronal connectivity, and finally evoke neuronal apoptosis [298][299][300][301]. The ER constitutes a dynamic cellular organelle that plays a major role in protein synthesis, posttranslational modification, trafficking, lipids and steroids synthesis, carbohydrate metabolism, calcium homeostasis, as well as efficient drugs metabolism [302][303][304].…”
Section: Endoplasmic Reticulum Stress and The Unfolded Protein Responmentioning
confidence: 99%
“…However, if the ER stress is severe and prolonged, the pro-adaptive branch of the UPR may switch into the pro-apoptotic one. Thus, there is ample evidence that targeting components of the UPR signaling pathway may constitute a novel, promising treatment strategy against ER stress-dependent human neurodegenerative pathologies [301,313,314].…”
Section: Endoplasmic Reticulum Stress and The Unfolded Protein Responmentioning
confidence: 99%